The Effect of Organizational Culture, Competence, Compensation, and Work Motivation on Employee Performance at Bank Syariah Indonesia Jepara Branch Office - Choirunisa Oktaviani , Livia; Sam’ani; Arumsari , Vita (Tazkia Islamic University College, 2023)
This study aims to analyze and obtain empirical evidence regarding the effect of organizational culture, competence, compensation, and work motivation on employee performance in Bank Syariah Indonesia Sub-Branch Office Jepara Pemuda 1 and Sub-Branch Office Jepara Pemuda 2 either simultaneously or partially. The population of the data used in this study includes all employees consisting of two branch offices, namely Bank Syariah Indonesia, Jepara Pemuda 1 Sub-Branch Office and Jepara Pemuda 2 Sub-Branch Office as many as 36 employees. Primary data obtained through the distribution of questionnaires. The data analysis model uses multiple linear regression analysis model. The results of the analysis and discussion show that the variables of organizational culture, competence, compensation, and work motivation simultaneously and partially have a significant effect on employee performance at Bank Syariah Indonesia Sub-Branch Office Jepara Pemuda 1 and Sub-Branch Office Jepara Pemuda 2.